Simbionte: interações artificiais nas artes visuais - Almeida Neto, Orlando Matos de (2025)
This work presents the use of generative digital tools in interaction with traditional means of image production. It explores, from a multidisciplinary perspective, the foundations that sustain the intersections between artificial intelligence algorithms and the visual arts as collaborative instances, capable of expanding the horizons of artistic creation and making. It seeks to understand, investigate, and document the author’s artistic procedures through drawings, watercolors, digital paintings, videos, illustrations, tattoos, and texts. The results establish a dialogue between the artist and technology, considering its multiple dimensions, including the ethical implications involved in the use of artificial intelligence in image creation. This study, grounded in the thinking of Aby Warburg, Arlindo Machado, Fayga Ostrower, Jacques Rancière and Carolina Loich, contributes to the understanding of the transformative potential of algorithmic tools in image production and to the advancement of knowledge at the intersection of art, sensibility, and technology.